2020
DOI: 10.30910/turkjans.740195
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’nin Bingöl ilinde Virüs Belirtisi Gösteren Kavun Bitkilerinde Hıyar mozaik virüsü ve Karpuz mozaik virüsünün Varlığı ve Filogenetik Yakınlıkları

Abstract: In the surveys conducted in the province of Bingöl in 2019, melon plants exhibiting foliar deformations, mosaic pattern in different concentrations of green, and vein banding were noticed. Melon specimens were gathered and screened by RT-PCR using capsid protein (CP) gene-specific primer sets to characterize and to ascertain the possible viral agents related to infected plants. About 657 bp and 822 bp DNA fragments were observed in the agarose gel of infected plants, confirming the presence of Cucumber mosaic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
(33 reference statements)
0
2
0
1
Order By: Relevance
“…As a result of RT-PCR performed using primer sets specific to the coat protein (CP) gene, it was determined that the partial coat protein gene length contained 657 bp [29]. Furthermore, two separate research have shown the existence of CMV isolate in the region of Diyarbakır.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of RT-PCR performed using primer sets specific to the coat protein (CP) gene, it was determined that the partial coat protein gene length contained 657 bp [29]. Furthermore, two separate research have shown the existence of CMV isolate in the region of Diyarbakır.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the research in the world shown that CMV subgroup I divided into two subgroups (Ia and Ib) with the analysis of non-protein coding regions at the 5' end and the CP gene [6]. Previous studies have shown the presence of CMV infections in various hosts in Turkey, as described by several researchers [29,32,36,37,38]. A few studies have shown that subgroup IA isolates are frequently observed in molecular investigations carried with CMV [34,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…CMV were clustered three molecular group as IA, IB, and II based on the information about different regions of the genome (Eiras et al, 2004). In previous studies in Turkey, CMV isolates have been determined in different plant hosts (Ergun et al, 2013;Karanfil and Korkmaz 2017;Guneş and Gumuş 2019;Guller and Usta 2020;Yeşil 2020). Most of the Turkish CMV isolates fell into the subgroup IA as the Turkish CMV isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the Turkish CMV isolates fell into the subgroup IA as the Turkish CMV isolates. Two CMV isolates from cowpea and tobacco crops in Turkey were classified into the subgroup IB (Karanfil and Korkmaz 2017;Guller and Usta 2020). Further sequence data are needed to characterize the population structure of CMV from Turkey and other countries.…”
Section: Discussionmentioning
confidence: 99%
“…Kabakgilleri enfekte eden virüslerden bazıları yaygın olarak çalışılırken, yeni bulunan bazı virüslerin ise enfeksiyonlarının ne derecede önemli ve yaygın olduğu ise bilinmemektedir. Ülkemizde gerçekleştirilen çalışmalar sonucunda kabakgillerde enfeksiyon meydana getiren çok sayıda virüs hastalığı tanımlanmıştır (Köklü ve Yilmaz, 2006;Kamberoglu ve ark., 2016;Güller ve Usta, 2020;Karanfil, 2022). Bunlar arasından en yaygın olarak tespit edilen virüslerden bazılarının zucchini yellow mosaic virus, watermelon mosaic virus ve cucumber mosaic virus (Topkaya ve ark., 2019;Yeşil, 2021;Karanfil ve Korkmaz, 2021) olduğu bildirilmiştir.…”
Section: Introductionunclassified